Characterisation of anti-pseudomonad activity of hyper-arid Micromonospora species. Issue 7 (10th July 2020) - Mark, David; DeWald, Jan; Dorador, Cristina; Tucker, Nicholas; Herron, Paul
Abstract : The opportunistic pathogen Pseudomonas aeruginosa is a major cause of nosocomial infections, and has been categorised by the World Health Organisation as a "Priority 1: Critical" target for research and development of novel antibiotics owing to its intrinsic multi-resistance and ability to acquire novel resistance mechanisms. One strategy for discovering novel antibiotics is the identification and characterisation of metabolites with antimicrobial activity. Members of the bacterial phylum Actinobacteria are historic source of these metabolites, in particular the genus Streptomyces . However, other genera have not received this same level of interest despite sharing the capacity to biosynthesise a diverse array of metabolites. One such genus is Micromonospora, responsible for production of the broad-spectrum aminoglycoside antibiotic gentamicin ( M. purpurea ). Here we present three Micromonospora species isolated from the Atacama Desert, Chile; that possess anti-pseudomonad bioactivity inducible by culture on International Streptomyces Project (ISP) Media. In addition, preliminary data indicates that this activity can be affected by the addition of P. aeruginosa conditioned media. In parallel, short-read Illumina sequencing was used to assemble draft genomes for these strains, enabling antiSMASH analysis of putative biosynthetic gene clusters. In addition to this, estimated Average Nucleotide Identity (ANI) as calculated by the autoMLST server indicates that these strains may all be novel Micromonospora species. The results of this work serve to highlight the biosynthetic capacity of an understudied genus of bacteria, as well as the value of examining underexplored environments and habitats in the search for novel bioactive molecules.